Hubungan Usia Demensia Dan Kemampuan Fungsional Pada Lansia - Sri Suwarni; Setiawan Setiawan; M. Mudadsir Syatibi (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Age, Dementia, Functional Ability, The Elderly. Increased life expectancy figures and the high cost of care for the elderly with dementia was associated with decreased functional ability to know how dependent elderly people in their daily activities. To determine the relationship of age, dementia and functional ability in the elderly. The study design was a descriptive study with observational analytic method with cross sectional study, done in parlors Wredha Dharma Bhakti Surakarta with 32 elderly subjects who met the inclusion criteria, age range 61-85 years. Dementia is measured using the Mini Mental State Examination (MMSE) and functional ability with Groningen Activity Restriction Scale (GARS). The results of statistical tests test the relationship (1) between age and dementia, p = 0.099 and r = - 0.297, meaning no meaningful relationship, negative and weak between the two variables. (2) between age and functional abilities, p = 0.000 and r = 0.699, which means that there is a meaningful relationship, positive and strong between the two variables. (3) between dementia with functional ability, p = 0.002 and r = - 0.535, meaning that there is a meaningful relationship, negative and strong between the two variables. there is no relationship of age on dementia but there is a strong relationship between age and functional ability and dementia of the functional ability of the elderly. Mean age was not linear with the increase in the incidence of dementia, but age and dementia are the root causes deterioration of functional ability in the elderly. Physiotherapy with various modalities that exist, can play a role to help maintain the functional capability of the elderly so that the slogan of healthy aging can be realized.